Estimativas de parâmetros genéticos em maxixe (Cucumis anguría L.) - Paiva, Waldelice Oliveira de (Acta Amazonica, 1984)
In 64 half-sib families of west Indian gerkin (Cucianiò angu&ia L.)the genotypic vaniation wasquite large for number and yield/ plant bat low for fruit weight. The heritability (h2h.s) wasestimated as 79.38%, 33.17% and 71.00% for fruit number weight and yield peA plant respectively. Genetic advance expected by selection of the 15% of the best families, in nelation to the evaluated population washiger (4 033%, 5 0661 and 42,263%). Phenotypic and genotypic correlation coefficients indicated higher and positive values for fruit number X yield and fruit weight X yield. For improvment of yield irit suggested that simple methods of selection have been used.